METHODOLOGIES OF LANGUAGE TEACHING: THEIR MERITS AND DEMERITS - Begizova Madina Karimovna (Western European Studies, 2023)
The most important of all the factors that ensure a successful language learning is knowledge of teaching methods. In the article it is stressed that application of modern methods and approaches in the process of teaching, knowledge of not only of the plus sides but also minuses of the methods being utilized can considerably contribute both to teacher’s performance as well as students’ growth in overall adequate mastery of the language they learn
Keywords: method; approach; total physical response method